Effects of Functional Electrical Stimulation Based on Walking Pattern with Different Treatment Time on Lower Limb Function in Stroke Patients：A Randomized Controlled Study - XUE Jingjing; KONG Huimin; LIAO Meixin; XUE Yunlian; XIAO Lingjun (康复学报)
ObjectiveFocusing on the intelligent and multi-channel functional electrical stimulation (FES) based on normal walking patterns, we explored the correlation between therapeutic effect and stimulating time for improving lower extremity motor function of stroke patients, to provide evidence for further clinical applications of FES based on walking patterns.MethodsThe Minimize software was used to divided 18 stroke patients randomly into a group treated with 60 min FES in walking pattern (9 patients, 60 min-stimulation group), and the rest were treated with 30 min FES in walking pattern (9 patients, 30 min-stimulation group). Both groups received conventional rehabilitation treatment. In addition, the 60 min-stimulation group received FES in walking pattern for 30 min and electric stimulation in the decumbent position for 30 min, while 30 min-stimulation group received FES in walking pattern for 30 min and placebo stimulation for 30 min. The electrical stimulation treatment was applied once per day, 5 days per week and totally 15 times. Participants' lower extremity motor functions and ability in daily activities were assessed via modified Ashworth scale (MAS), manual muscle test (MMT), Fugl-Meyer assessment-lower extremity (FMA-LE), Berg balance scale (BBS), 10 meter walk test (10MWT) and modified Barthel index (MBI) in 4 time points: before treatment, after treatments for 7 times, after treatments for 15 times and one month follow up.ResultsCompared with before treatment, MAS, MMT, FMA-LE and BBS were statistically different in two groups after treatments for 7 times, 15 times and one month follow up (P<0.05). In the 60 min-stimulation group, statistically significant differences in MBI assessments appeared in 3 time points after treatment (P<0.05), while the 30 min-stimulation group only had statistical differences after treatments for 7 times and 15 times (P<0.05). Besides, the 60 min-stimulation group had statistically significant differences in walking speed after treatments for 7 times and 15 times, while the 30 min-stimulation group only had a statistically significant difference after treatments for 15 times (P<0.05). Comparing between the two groups, the 60 min-stimulation group showed more significantly improvements in MAS and walking speed after treatments for 7 times (P<0.05); After treatments for 15 times, differences were found in MAS, FMA-LE and MBI (P<0.05) and there were still statistical differences between MAS and MBI during the following-up (P<0.05).ConclusionThe intelligent, multi-channel functional electrical stimulation can effectively improve the lower extremity motor function, balance, walking and daily life activities of stroke patients. While prolonged stimulation time (from 30 min-stimulation to 60 min-stimulation) not only can enhance the therapeutic effect of reducing muscle tone, improving motor function of the affected lower limb, improving gait speed and self-care ability, but also can prolong the duration of the efficacy of self-care ability.